(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A mathematical model is developed by treating blood as a non-Newtonian fluid, unsteady MHD flow with Hall current in a multi-stenosed artery. The governing equation are solved by using perturbation technique. The fluid is subjected to the chemical reaction with mass transfer and velocity through the porous medium is consideration. The analytical solutions for velocity, temperature, concentration, shear stress and shear rate are calculated. The numerical solutions are graphically depicted for physical parameters.